Idiopathic Pulmonary Fibrosis: Epidemiology, Clinical Features, Prognosis, and Management - Lynch, Joseph P., III; Huynh, Richard H.; Fishbein, Michael C.; Saggar, Rajan; Belperio, John A.; Weigt, S. Sam (Seminars in Respiratory and Critical Care Medicine, 2016)
Idiopathic pulmonary fibrosis (IPF) is a specific form of chronic interstitial lung pneumonia associated with the histologic pattern of usual interstitial pneumonia (UIP). Although UIP is a distinct histologic lesion, this histologic pattern is not specific for IPF and can also be found in other diseases (e.g., connective tissue disease and asbestosis). Clinical features of IPF include progressive cough, dyspnea, restrictive ventilatory defect, and progressive fibrosis and destruction of the lung parenchyma. IPF is rare (13–42 cases/100,000), and primarily affects older adults (>50 years of age). The diagnosis of IPF often requires surgical lung biopsy, but the diagnosis can be affirmed with confidence in some patients provided the results of computed tomographic (CT) scans and clinical features are consistent. The clinical course is variable, but inexorable progression (typically over months to years) is typical. Mean survival from the onset of symptoms approximates 3 to 5 years. Medical treatment is only modestly effective, primarily by slowing the rate of disease progression. Lung transplantation is the best therapeutic option.
Keywords: cryptogenic fibrosing alveolitis; idiopathic pulmonary fibrosis; usual interstitial pneumonia